A negative electrode sheet, a method for manufacturing the negative electrode sheet, and a battery cell

By setting graphite and silicon anode layers on both sides of the current collector respectively, and using their optimal formulations and components, the problem of increased particle gap and breakage caused by the difference in expansion rates between graphite and silicon anode during charging and discharging was solved, achieving high pressure, low expansion and improved performance.

CN117457850BActive Publication Date: 2026-11-06广东省豪鹏新能源科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311439929.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2026-11-06
Estimated Expiration
2043-10-31

AI Technical Summary

Technical Problem

In existing technologies, graphite and silicon anodes have vastly different expansion rates during charging and discharging, leading to increased particle spacing and particle breakage, making it difficult to leverage their respective characteristics. Furthermore, their compaction density requirements are inconsistent, making it difficult to meet the ever-increasing energy density demands.

Method used

Graphite anode layer and silicon anode layer are respectively disposed on both sides of the current collector. The graphite anode layer is formed by rolling, while the silicon anode layer is not rolled. The mass ratio of the active materials of the two is 5:95 to 50:50. They adopt their respective optimal formulas and components, such as adding single-walled carbon nanotubes to the silicon anode slurry and matching a highly elastic binder.

Benefits of technology

This approach achieves high compaction and low expansion in the graphite anode layer, while reserving expansion buffer space in the silicon anode layer. This reduces the problem of increased particle gaps, prevents particle breakage, improves performance, and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117457850B_ABST
    Figure CN117457850B_ABST
Patent Text Reader

Abstract

This invention relates to the field of lithium-ion battery cell technology, specifically to a negative electrode sheet, a method for preparing the negative electrode sheet, and a battery cell thereof. The negative electrode sheet includes a current collector, a silicon negative electrode layer, and a graphite negative electrode layer. The silicon negative electrode layer is laid on one side of the current collector, and the graphite negative electrode layer is laid on the other side of the current collector; the graphite negative electrode layer is formed by roll forming, while the silicon negative electrode layer is not formed by roll forming; the mass ratio of active materials in the silicon negative electrode layer to the graphite negative electrode layer is 5:95 to 50:50. The graphite negative electrode layer and the silicon negative electrode layer are located on opposite sides of the current collector, and they do not interfere with each other at all. During the slurry preparation, each can use its optimal formula, adding different components according to their different characteristics; the expansion stress of the silicon negative electrode layer will not affect the graphite negative electrode layer, causing the negative electrode particles to break.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery cell technology, and in particular to a negative electrode sheet, a method for preparing the negative electrode sheet, and a battery cell thereof. Background Technology

[0002] As research on lithium-ion battery technology continues to deepen, the development of graphite systems has reached its limit. Silicon anodes, due to their extremely high specific capacity, can improve the energy density of lithium-ion batteries and have received widespread attention. Silicon anode systems have also gradually gained importance and developed applications.

[0003] Currently, the main applications of silicon anodes include silicon-oxygen anodes, nano-silicon anodes, and silicon-carbon anodes. However, due to the significant difference in expansion rates between graphite and silicon anodes during charging and discharging (graphite expansion rate is approximately 20%, while silicon anode expansion rate is approximately 300%), when the two are mixed together, the expansion of the silicon anode generates significant deformation stress on the graphite anode, leading to increased interparticle spacing and further volume expansion. Simultaneously, the immense stress causing interparticle compression may result in particle breakage, affecting cell performance. Furthermore, graphite anodes can achieve high compaction, while silicon anodes, to mitigate volume expansion deformation, typically employ hollow framework or porous buffer designs, resulting in lower compaction densities. This leads to inconsistent compaction density requirements between the two materials. Additionally, due to the inconsistency in surface functional groups, graphite and silicon anodes are suited to different binder systems, meaning that directly mixing them cannot fully utilize the unique characteristics of each material.

[0004] Currently, the main solutions to the aforementioned problems are optimizing the anode material formulation or layering graphite and silicon anodes, aiming to suppress the expansion of silicon anode particles or reduce their impact. However, with the increasing demand for energy density, the silicon content and compaction requirements of the anode are rising, making these solutions increasingly inadequate. Summary of the Invention

[0005] The technical problem to be solved by the embodiments of the present invention is to provide a negative electrode sheet, a method for preparing the negative electrode sheet and its battery cell, so as to solve the problems of volume expansion of silicon negative electrodes, breakage of negative electrode particles, and difficulty in graphite negative electrodes and silicon negative electrodes giving full play to their own characteristics in the prior art.

[0006] This invention discloses a negative electrode sheet, comprising a current collector, a silicon negative electrode layer, and a graphite negative electrode layer; the silicon negative electrode layer is laid on one side of the current collector, and the graphite negative electrode layer is laid on the other side of the current collector; the graphite negative electrode layer is formed by roll forming, while the silicon negative electrode layer is not formed by roll forming; the mass ratio of active materials in the silicon negative electrode layer and the graphite negative electrode layer is 5:95 to 50:50.

[0007] Optionally, by weight percentage, the silicon anode layer comprises 90%-95% silicon anode, 0%-1% conductive agent, 0%-2% CMC, and 4%-8% binder.

[0008] Optionally, by weight percentage, the graphite anode layer comprises 95%-98% graphite, 0%-1% conductive agent, 0.5%-2% CMC, and 0.5%-2.5% binder.

[0009] Optionally, the mass ratio of the active materials in the silicon anode layer to the graphite anode layer is 5:95 to 30:70.

[0010] Optionally, the areal density of the silicon anode layer is 10-40 g / m². 2 The areal density of the graphite anode layer is 50-200 g / m³. 2 .

[0011] Optionally, the areal density of the silicon anode layer is 19.2 g / m². 2 The areal density of the graphite anode layer is 126 g / m³. 2 .

[0012] This invention also discloses a method for preparing a negative electrode, comprising the following steps:

[0013] Preparation of silicon anode slurry;

[0014] Preparation of graphite anode slurry;

[0015] The graphite negative electrode slurry is coated on one side of the current collector and rolled to obtain the graphite negative electrode layer.

[0016] The silicon anode paste is coated onto the other side of the current collector without rolling to obtain the silicon anode layer.

[0017] The graphite anode layer and silicon anode layer are dried, and then slit and tabs are welded to obtain the anode sheet;

[0018] The mass ratio of active materials in the silicon anode layer to the graphite anode layer is 5:95 to 50:50.

[0019] Optionally, the silicon anode layer comprises 90%-95% silicon anode, 0%-1% conductive agent, 0%-2% CMC, and 4%-8% binder; the graphite anode layer comprises 95%-98% graphite, 0%-1% conductive agent, 0.5%-2% CMC, and 0.5%-2.5% binder.

[0020] Optionally, the areal density of the silicon anode layer is 10-40 g / m². 2 The areal density of the graphite anode layer is 50-200 g / m³. 2 .

[0021] The present invention also discloses a battery cell, comprising a negative electrode, a positive electrode, and a separator as described above.

[0022] Compared with the prior art, the beneficial effects of the negative electrode sheet provided by the embodiments of the present invention are as follows: The negative electrode sheet preparation method of the present invention sets the graphite negative electrode layer and the silicon negative electrode layer on both sides of the current collector, completely separating the two. Furthermore, the graphite particles have low expansion, and the graphite negative electrode layer is formed by rolling, which can achieve high compaction and low expansion; while the silicon negative electrode layer is not formed by rolling, and the silicon negative electrode particles have low compaction, which can reserve expansion buffer space and reduce the problem of increased particle gap caused by the difference in expansion rate. Most importantly, the graphite negative electrode layer and the silicon negative electrode layer are set on both sides of the current collector, and the two will not interfere with each other at all. During the slurry preparation, each can use its optimal formula, adding different components according to their different characteristics. For example, single-walled carbon nanotubes can be completely added to the silicon negative electrode slurry, while matching a high-elasticity binder to improve performance; the expansion stress of the silicon negative electrode layer will not affect the graphite negative electrode layer, causing the negative electrode particles to break. Attached Figure Description

[0023] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. In the accompanying drawings:

[0024] Figure 1 This is a schematic diagram of the negative electrode sheet according to an embodiment of the present invention.

[0025] The labels for the attached figures are as follows:

[0026] 1. Current collector; 2. Silicon anode layer; 3. Graphite anode layer. Detailed Implementation

[0027] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The preferred embodiments of the present invention will now be described in detail with reference to the accompanying drawings.

[0028] This invention provides a negative electrode sheet, such as... Figure 1 As shown, the negative electrode sheet includes a current collector 1, a silicon negative electrode layer 2, and a graphite negative electrode layer 3. The silicon negative electrode layer 2 is laid on one side of the current collector 1, and the graphite negative electrode layer 3 is laid on the other side of the current collector 1; the graphite negative electrode layer 3 is formed by roll forming, while the silicon negative electrode layer 2 is not formed by roll forming; the mass ratio of the active materials of the silicon negative electrode layer 2 and the graphite negative electrode layer 3 is 5:95 to 50:50.

[0029] The negative electrode sheet of this invention has a graphite negative electrode layer 3 and a silicon negative electrode layer 2 respectively disposed on both sides of the current collector 1, completely separated from each other. Furthermore, the graphite particles have low expansion, and the graphite negative electrode layer 3 is formed by rolling, achieving high compaction and low expansion; while the silicon negative electrode layer 2 is not formed by rolling, resulting in low compaction between silicon negative electrode particles, allowing for reserved expansion buffer space and reducing the problem of increased particle gaps caused by differences in expansion rates. Most importantly, the graphite negative electrode layer 3 and the silicon negative electrode layer 2 are disposed on both sides of the current collector 1, ensuring no interference between them. During slurry preparation, each can use its optimal formulation, adding different components based on their different characteristics. For example, single-walled carbon nanotubes can be completely added to the silicon negative electrode slurry, while simultaneously matching a highly elastic binder to improve performance. The expansion stress of the silicon negative electrode layer 2 will not affect the graphite negative electrode layer 3, preventing the negative electrode particles from breaking.

[0030] However, if the graphite anode layer 3 and the silicon anode layer 2 are simply layered, for example, if only the silicon anode layer 2 is placed on top of the graphite anode layer 3, the silicon anode layer 2 will still be in contact with the graphite anode layer 3. When the silicon anode layer 2 expands, its expansion stress will still compress the graphite anode layer 3, causing the particles to break. Furthermore, because the graphite anode layer 3 and the silicon anode layer 2 are laid out sequentially and their formulations and proportions are different, the adhesion between the graphite anode layer 3 and the silicon anode layer 2 is poor. Cracks or even separation can easily occur at their intersection, leading to an increase in the resistance of the anode sheet and a deterioration in performance.

[0031] Furthermore, the mass ratio of active materials in the silicon anode layer 2 to the graphite anode layer 3 is 5:95 to 50:50, meaning the amount of active material in the silicon anode layer 2 is much smaller than, and at most does not exceed, the amount of active material in the graphite anode layer 3. This significantly reduces the impact of the expansion of the silicon anode layer 2 on the overall performance of the anode sheet, resulting in better anode sheet performance. Specifically, the mass ratio of active materials in the silicon anode layer 2 to the graphite anode layer 3 can be 5:95, 10:90, 15:85, 20:80, 25:75, 30:70, 35:65, 40:60, 45:55, or 50:50. Preferably, the mass ratio of active materials in the silicon anode layer 2 to the graphite anode layer 3 is 5:95 to 30:70. More preferably, the mass ratio of active materials in the silicon anode layer 2 to the graphite anode layer 3 is 12.8:87.2.

[0032] Specifically, by mass percentage, the silicon anode layer 2 comprises 90%-95% silicon anode, 0%-1% conductive agent, 0%-2% CMC, and 4%-8% binder. For example, the proportion of silicon anode can be 90%, 91%, 92%, 93%, 94%, or 95%; the proportion of conductive agent can be 0%, 0.2%, 0.4%, 0.6%, 0.8%, or 1%; the proportion of CMC can be 0%, 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, or 2%; and the proportion of binder can be 4%, 5%, 6%, 7%, or 8%. In the silicon anode layer 2, the silicon anode can be one or more of the following: silicon-oxygen anode material (SiOx), silicon-carbon anode material (SiC), nano-silicon; the conductive agent can be one or more of the following: carbon black, acetylene black, single-walled / multi-walled carbon nanotubes, carbon nanofibers; the CMC can be one or more of the following: carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose; the binder can be one or more of the following: styrene-butadiene rubber (SBR), polyacrylic acid (PAA), lithium polyacrylate (PAA-Li), polyvinyl alcohol (PVA), styrene-acrylic emulsion, sodium alginate.

[0033] By mass percentage, the graphite anode layer 3 comprises 95%-98% graphite, 0%-1% conductive agent, 0.5%-2% CMC, and 0.5%-2.5% binder. For example, the percentage of graphite can be 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, or 98%; the percentage of conductive agent can be 0%, 0.2%, 0.4%, 0.6%, 0.8%, or 1%; the percentage of CMC can be 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, or 2%; and the percentage of binder can be 0.5%, 1%, 1.5%, 2%, or 2.5%. In the silicon anode layer 2, graphite can be one or more of artificial graphite, natural graphite, hard carbon, soft carbon, etc.; the conductive agent can be one or more of carbon black, acetylene black, single-walled / multi-walled carbon nanotubes, carbon nanofibers, etc.; CMC can be one or more of carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, etc.; the binder can be one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), lithium polyacrylate (PAA-Li), polyvinyl alcohol (PVA), styrene-acrylic emulsion, sodium alginate, etc.

[0034] Since the graphite electrode layer and silicon anode layer 2 of the present invention are respectively placed on both sides of the current collector 1, in the above scheme, compared with the graphite anode layer 3 having a binder ratio of only 0.5%-2.5%, the silicon anode layer 2 has a binder ratio of 4%-8%. The silicon anode layer 2, using a high-adhesion formulation, can more effectively suppress particle expansion. Furthermore, since silicon anodes typically require the addition of single-walled carbon nanotubes to improve cycle performance, while graphite anodes do not, the conductive agent of the graphite anode layer 3 does not contain single-walled carbon nanotubes. This allows the single-walled carbon nanotubes to be completely added to the silicon anode layer 2, enabling more efficient and rational utilization of the expensive single-walled carbon nanotubes and reducing costs.

[0035] Specifically, the areal density of the silicon anode layer 2 is 10-40 g / m². 2 The areal density of graphite anode layer 3 is 50-200 g / m³. 2 For example, the areal density of silicon anode layer 2 can be 10 g / m². 2 15g / m 2 20g / m 2 25g / m 2 30g / m 2 35g / m 2 40g / m 2 The areal density of graphite anode layer 3 can be 50 g / m³. 2 70g / m 2 90g / m 2 100g / m 2 120g / m 2 140g / m 2 160g / m 2 180g / m 2 200g / m 2 Preferably, the areal density of the silicon anode layer 2 is 19.2 g / m². 2 The areal density of graphite anode layer 3 is 126 g / m³. 2 .

[0036] This invention also discloses a method for preparing a negative electrode, comprising the following steps:

[0037] S100: Preparation of silicon anode slurry;

[0038] S200: Preparation of graphite anode slurry;

[0039] S300: The graphite negative electrode slurry is coated on one side of the current collector and rolled to obtain the graphite negative electrode layer;

[0040] S400: The silicon anode paste is coated on the other side of the current collector without rolling to obtain the silicon anode layer;

[0041] S500: Dry the graphite anode layer and silicon anode layer, and then cut and weld the tabs to obtain the anode sheet;

[0042] The mass ratio of active materials in the silicon anode layer to the graphite anode layer is 5:95 to 50:50.

[0043] In step S100, the silicon anode slurry formulation, by mass percentage, comprises 90%-95% silicon anode, 0%-1% conductive agent, 0%-2% CMC, and 4%-8% binder (based on silicon anode layer 2). The silicon anode can be one or more combinations of silicon-oxygen anode material (SiOx), silicon-carbon anode material (SiC), nano-silicon, etc.; the conductive agent can be one or more combinations of carbon black, acetylene black, single-walled / multi-walled carbon nanotubes, carbon nanofibers, etc.; the CMC can be one or more combinations of carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, etc.; the binder can be one or more combinations of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), lithium polyacrylate (PAA-Li), polyvinyl alcohol (PVA), styrene-acrylic emulsion, sodium alginate, etc.

[0044] In step S200, the graphite anode slurry comprises, by mass percentage, 95%-98% graphite, 0%-1% conductive agent, 0.5%-2% CMC, and 0.5%-2.5% binder (based on graphite anode layer 3). Graphite can be one or more combinations of artificial graphite, natural graphite, hard carbon, soft carbon, etc.; the conductive agent can be one or more combinations of carbon black, acetylene black, single-walled / multi-walled carbon nanotubes, carbon nanofibers, etc.; the CMC can be one or more combinations of carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, etc.; and the binder can be one or more combinations of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), lithium polyacrylate (PAA-Li), polyvinyl alcohol (PVA), styrene-acrylic emulsion, sodium alginate, etc.

[0045] Specifically, the areal density of the silicon anode layer 2 is 10-40 g / m². 2 The areal density of graphite anode layer 3 is 50-200 g / m³. 2 For example, the areal density of silicon anode layer 2 can be 10 g / m². 2 15g / m 2 20g / m 2 25g / m 2 30g / m 2 35g / m 2 40g / m 2 The areal density of graphite anode layer 3 can be 50 g / m³. 2 70g / m 2 90g / m 2 100g / m 2 120g / m2 140g / m 2 160g / m 2 180g / m 2 200g / m 2 Preferably, the areal density of the silicon anode layer 2 is 19.2 g / m². 2 The areal density of graphite anode layer 3 is 126 g / m³. 2 .

[0046] The negative electrode preparation method of the present invention involves disposing a graphite negative electrode layer 3 and a silicon negative electrode layer 2 on opposite sides of a current collector 1, completely separating them. Furthermore, the graphite particles exhibit low expansion, and the graphite negative electrode layer 3, formed by rolling, achieves high compaction and low expansion. Conversely, the silicon negative electrode layer 2, not formed by rolling, exhibits low compaction between silicon negative electrode particles, allowing for reserved expansion buffer space and reducing the problem of increased particle gaps caused by differences in expansion rates. Most importantly, the graphite negative electrode layer 3 and the silicon negative electrode layer 2, being disposed on opposite sides of the current collector 1, do not interfere with each other. During slurry preparation, each can employ its optimal formulation, adding different components based on their different characteristics. For example, single-walled carbon nanotubes can be completely added to the silicon negative electrode slurry, while simultaneously using a highly elastic binder to enhance performance. The expansion stress of the silicon negative electrode layer 2 will not affect the graphite negative electrode layer 3, preventing the negative electrode particles from breaking.

[0047] The mass ratio of active materials in silicon anode layer 2 to graphite anode layer 3 is 5:95 to 50:50, meaning that the amount of active material in silicon anode layer 2 is much less than that in graphite anode layer 3, and at most does not exceed that in graphite anode layer 3. This can significantly reduce the impact of the expansion of silicon anode layer 2 on the overall anode sheet, resulting in better performance of the anode sheet.

[0048] Furthermore, since the graphite electrode layer and silicon anode layer 2 of the present invention are respectively placed on both sides of the current collector 1, in the above scheme, compared with the graphite anode layer 3 having a binder ratio of only 0.5%-2.5%, the silicon anode layer 2 has a binder ratio of 4%-8%. The silicon anode layer 2 uses a high-adhesion formulation, which can more effectively suppress particle expansion. Further, since silicon anodes typically require the addition of single-walled carbon nanotubes to improve cycle performance, while graphite anodes do not, the conductive agent of the graphite anode layer 3 does not contain single-walled carbon nanotubes. This allows the single-walled carbon nanotubes to be completely added to the silicon anode layer 2, making more efficient and rational use of the expensive single-walled carbon nanotubes and reducing costs.

[0049] The present invention also discloses a battery cell, comprising a negative electrode, a positive electrode, and a separator as described above.

[0050] The technical solution of the present invention will be described in detail below through specific embodiments and comparative examples.

[0051] Example 1

[0052] In this embodiment, the mass ratio of silicon-oxygen anode to artificial graphite is 12.8:87.2.

[0053] Graphite slurry preparation and coating: A graphite slurry was prepared according to the following solid content weight ratios: artificial graphite: 98%, CMC-Li: 1%, SBR: 1%. The coating process was completed on one side of the copper foil, with a coating surface density of 126 g / m². 2 After the single-sided graphite slurry coating is completed, a rolling process is performed. After the rolling process is completed, the roll is returned to the coating process for silicon anode slurry coating.

[0054] Silicon anode slurry preparation and coating: The silicon anode slurry was prepared according to the following solid content weight ratio: silicon-oxygen anode: 94%, single-walled carbon nanotubes: 0.1%, PAA-Li: 5.9%. The coating process was completed on the other side of the copper foil, with a coating surface density of 19.2 g / m². 2 The coated electrode sheets are no longer rolled and are directly processed into subsequent slitting and sheet making processes.

[0055] Cell fabrication: The negative electrode sheet prepared in the above steps is combined with the corresponding positive electrode sheet for subsequent winding, liquid injection, and formation and capacity testing to complete the cell fabrication.

[0056] Example 2

[0057] In this embodiment, the mass ratio of silicon-carbon anode to artificial graphite is 8.3:91.7.

[0058] Graphite slurry preparation and coating: A graphite slurry was prepared according to the following solid content weight ratios: artificial graphite: 98%, CMC-Li: 1%, SBR: 1%. The coating process was completed on one side of the copper foil, with a coating surface density of 132 g / m². 2 After the single-sided graphite slurry coating is completed, a rolling process is performed. After the rolling process is completed, the roll is returned to the coating process for silicon anode slurry coating.

[0059] Silicon anode slurry preparation and coating: The silicon anode slurry was prepared according to the following solid weight ratio: silicon-carbon anode: 94%, single-walled carbon nanotubes: 0.1%, PAA-Li: 5.9%. The coating process was completed on the other side of the copper foil, with a coating surface density of 12.5 g / m². 2 The coated electrode sheets are no longer rolled and are directly processed into subsequent slitting and sheet making processes.

[0060] Cell fabrication: The negative electrode sheet prepared in the above steps is combined with the corresponding positive electrode sheet for subsequent winding, liquid injection, and formation and capacity testing to complete the cell fabrication.

[0061] Example 3

[0062] In this embodiment, the mass ratio of silicon-carbon anode to artificial graphite is 13.2:86.8.

[0063] Graphite slurry preparation and coating: A graphite slurry was prepared according to the following solid content weight ratios: artificial graphite: 98%, CMC-Li: 1%, SBR: 1%. The coating process was completed on one side of the copper foil, with a coating surface density of 109 g / m². 2 After the single-sided graphite slurry coating is completed, a rolling process is performed. After the rolling process is completed, the roll is returned to the coating process for silicon anode slurry coating.

[0064] Silicon anode slurry preparation and coating: The silicon anode slurry was prepared according to the following solid content weight ratio: silicon-carbon anode: 94%, single-walled carbon nanotubes: 0.1%, PAA-Li: 5.9%. The coating process was completed on the other side of the copper foil, with a coating surface density of 17.3 g / m². 2 The coated electrode sheets are no longer rolled and are directly processed into subsequent slitting and sheet making processes.

[0065] Cell fabrication: The negative electrode sheet prepared in the above steps is combined with the corresponding positive electrode sheet for subsequent winding, liquid injection, and formation and capacity testing to complete the cell fabrication.

[0066] Example 4

[0067] In this embodiment, the mass ratio of silicon-carbon anode to artificial graphite is 20.2:79.8.

[0068] Graphite slurry preparation and coating: A graphite slurry was prepared according to the following solid content weight ratios: artificial graphite: 98%, CMC-Li: 1%, SBR: 1%. The coating process was completed on one side of the copper foil, with a coating surface density of 85 g / m². 2 After the single-sided graphite slurry coating is completed, a rolling process is performed. After the rolling process is completed, the roll is returned to the coating process for silicon anode slurry coating.

[0069] Silicon anode slurry preparation and coating: The silicon anode slurry was prepared according to the following solid content weight ratio: silicon-carbon anode: 94%, single-walled carbon nanotubes: 0.1%, PAA-Li: 5.9%. The coating process was completed on the other side of the copper foil, with a coating surface density of 22.4 g / m². 2 The coated electrode sheets are no longer rolled and are directly processed into subsequent slitting and sheet making processes.

[0070] Cell fabrication: The negative electrode sheet prepared in the above steps is combined with the corresponding positive electrode sheet for subsequent winding, liquid injection, and formation and capacity testing to complete the cell fabrication.

[0071] Example 5

[0072] In this embodiment, the mass ratio of silicon-carbon anode to artificial graphite is 30.6:69.4.

[0073] Graphite slurry preparation and coating: A graphite slurry was prepared according to the following solid content weight ratios: artificial graphite: 98%, CMC-Li: 1%, SBR: 1%. The coating process was completed on one side of the copper foil, with a coating surface density of 60 g / m². 2 After the single-sided graphite slurry coating is completed, a rolling process is performed. After the rolling process is completed, the roll is returned to the coating process for silicon anode slurry coating.

[0074] Silicon anode slurry preparation and coating: The silicon anode slurry was prepared according to the following solid content weight ratio: silicon-carbon anode: 94%, single-walled carbon nanotubes: 0.1%, PAA-Li: 5.9%. The coating process was completed on the other side of the copper foil, with a coating surface density of 27.6 g / m². 2 The coated electrode sheets are no longer rolled and are directly processed into subsequent slitting and sheet making processes.

[0075] Cell fabrication: The negative electrode sheet prepared in the above steps is combined with the corresponding positive electrode sheet for subsequent winding, liquid injection, and formation and capacity testing to complete the cell fabrication.

[0076] Example 6

[0077] In this embodiment, the mass ratio of silicon-carbon anode to artificial graphite is 45:55.

[0078] Graphite slurry preparation and coating: A graphite slurry was prepared according to the following solid content weight ratios: artificial graphite: 98%, CMC-Li: 1%, SBR: 1%. The coating process was completed on one side of the copper foil, with a coating surface density of 50 g / m². 2 After the single-sided graphite slurry coating is completed, a rolling process is performed. After the rolling process is completed, the roll is returned to the coating process for silicon anode slurry coating.

[0079] Silicon anode slurry preparation and coating: The silicon anode slurry was prepared according to the following solid content weight ratio: silicon-carbon anode: 94%, single-walled carbon nanotubes: 0.1%, PAA-Li: 5.9%. The coating process was completed on the other side of the copper foil, with a coating surface density of 32.3 g / m². 2 The coated electrode sheets are no longer rolled and are directly processed into subsequent slitting and sheet making processes.

[0080] Cell fabrication: The negative electrode sheet prepared in the above steps is combined with the corresponding positive electrode sheet for subsequent winding, liquid injection, and formation and capacity testing to complete the cell fabrication.

[0081] Comparative Example 1

[0082] Compared with Example 1, the types and proportions of graphite and silicon anodes are the same in this example. The difference is that the graphite and silicon anodes are mixed and used as a whole, and the two sides are no longer coated separately. The same surface density and slurry are used. After completion, subsequent processes such as roll forming and slitting are carried out.

[0083] In this embodiment, the mass ratio of silicon-oxygen anode to artificial graphite is 12.8:87.2.

[0084] Preparation and coating of silicon-carbon anode and artificial graphite blended slurry: The blended slurry was prepared according to the following solid weight ratio: artificial graphite + silicon-oxygen anode: 96%, carbon black: 0.9%, single-walled carbon nanotubes: 0.1%, CMC-Li: 1%, SBR: 2%. The coating process was completed on both sides of the copper foil, with a coating surface density of 73.7 g / m². 2 .

[0085] Cell fabrication: The negative electrode sheet prepared in the above steps is combined with the corresponding positive electrode sheet for subsequent winding, liquid injection, and formation and capacity testing to complete the cell fabrication.

[0086] Comparative Example 2

[0087] Compared with Example 2, the types and proportions of graphite and silicon anodes are the same in this example. The difference is that the graphite and silicon anodes are mixed and used as a whole, and the two sides are no longer coated separately. The same surface density and slurry are used. After completion, subsequent processes such as roll pressing and slitting are carried out. The overall preparation method is the same as that of Comparative Example 1. The difference is in the proportion of graphite and silicon anodes and the type of silicon anode.

[0088] In this embodiment, the mass ratio of silicon-carbon anode to artificial graphite is 8.3:91.7.

[0089] Preparation and coating of silicon-carbon anode and artificial graphite blend slurry: The blend slurry was prepared according to the following solid weight ratio: artificial graphite + silicon-carbon anode: 96%, carbon black: 0.9%, single-walled carbon nanotubes: 0.1%, CMC-Li: 1%, SBR: 2%. The coating process was completed on both sides of the copper foil, with a coating surface density of 73.7 g / m². 2 .

[0090] Cell fabrication: The negative electrode sheet prepared in the above steps is combined with the corresponding positive electrode sheet for subsequent winding, liquid injection, and formation and capacity testing to complete the cell fabrication.

[0091] Comparative Example 3

[0092] Compared with Example 3, the types and proportions of graphite and silicon anodes are the same in this example. The difference is that the graphite and silicon anodes are mixed and used as a whole, and the two sides are no longer coated separately. The same surface density and slurry are used. After completion, subsequent processes such as roll pressing and slitting are carried out. The overall preparation method is the same as that of Comparative Example 1. The difference is in the ratio of graphite and silicon anodes, the type of silicon anode, and the surface density.

[0093] In this embodiment, the mass ratio of silicon-carbon anode to artificial graphite is 13.2:86.8.

[0094] Preparation and coating of silicon-carbon anode and artificial graphite blend slurry: The blend slurry was prepared according to the following solid weight ratio: artificial graphite + silicon-carbon anode: 96%, carbon black: 0.9%, single-walled carbon nanotubes: 0.1%, CMC-Li: 1%, SBR: 2%. The coating process was completed on both sides of the copper foil, with a coating surface density of 64.3 g / m². 2 .

[0095] Cell fabrication: The negative electrode sheet prepared in the above steps is combined with the corresponding positive electrode sheet for subsequent winding, liquid injection, and formation and capacity testing to complete the cell fabrication.

[0096] Comparative Example 4

[0097] Compared with Example 4, the types and proportions of graphite and silicon anodes in this example are the same. The difference is that the graphite and silicon anodes are mixed and used as a whole, and the two sides are no longer coated separately. The same surface density and slurry are used. After completion, subsequent processes such as roll pressing and slitting are carried out. The overall preparation method is the same as that of Comparative Example 1. The difference lies in the ratio of graphite and silicon anodes, the type of silicon anode, and the surface density.

[0098] In this embodiment, the mass ratio of silicon-carbon anode to artificial graphite is 20.2:79.8.

[0099] Preparation and coating of silicon-carbon anode and artificial graphite blend slurry: The blend slurry was prepared according to the following solid weight ratio: artificial graphite + silicon-carbon anode: 96%, carbon black: 0.9%, single-walled carbon nanotubes: 0.1%, CMC-Li: 1%, SBR: 2%. The coating process was completed on both sides of the copper foil, with a coating surface density of 54.4 g / m². 2 .

[0100] Cell fabrication: The negative electrode sheet prepared in the above steps is combined with the corresponding positive electrode sheet for subsequent winding, liquid injection, and formation and capacity testing to complete the cell fabrication.

[0101] Comparative Example 5

[0102] Compared with Example 5, the types and proportions of graphite and silicon anodes are the same in this example. The difference is that the graphite and silicon anodes are mixed and used as a whole, and the two sides are no longer coated separately. The same surface density and slurry are used. After completion, subsequent processes such as roll pressing and slitting are carried out. The overall preparation method is the same as that of Comparative Example 1. The difference is in the proportion of graphite and silicon anodes, the type of silicon anode, and the surface density.

[0103] In this embodiment, the mass ratio of silicon-carbon anode to artificial graphite is 30.6:69.4.

[0104] Preparation and coating of silicon-carbon anode and artificial graphite blend slurry: The blend slurry was prepared according to the following solid weight ratio: artificial graphite + silicon-carbon anode: 96%, carbon black: 0.9%, single-walled carbon nanotubes: 0.1%, CMC-Li: 1%, SBR: 2%. The coating process was completed on both sides of the copper foil, with a coating surface density of 44.2 g / m². 2 .

[0105] Cell fabrication: The negative electrode sheet prepared in the above steps is combined with the corresponding positive electrode sheet for subsequent winding, liquid injection, and formation and capacity testing to complete the cell fabrication.

[0106] Comparative Example 6

[0107] Compared with Example 6, the types and proportions of graphite and silicon anodes in this example are the same. The difference is that the graphite and silicon anodes are mixed and used as a whole, and the two sides are no longer coated separately. The same surface density and slurry are used. After completion, subsequent processes such as roll pressing and slitting are carried out. The overall preparation method is the same as that of Comparative Example 1. The difference lies in the ratio of graphite and silicon anodes, the type of silicon anode, and the surface density.

[0108] In this embodiment, the mass ratio of silicon-carbon anode to artificial graphite is 45:55.

[0109] Preparation and coating of silicon-carbon anode and artificial graphite blend slurry: The blend slurry was prepared according to the following solid weight ratio: artificial graphite + silicon-carbon anode: 96%, carbon black: 0.9%, single-walled carbon nanotubes: 0.1%, CMC-Li: 1%, SBR: 2%. The coating process was completed on both sides of the copper foil, with a coating surface density of 35.1 g / m². 2 .

[0110] Cell fabrication: The negative electrode sheet prepared in the above steps is combined with the corresponding positive electrode sheet for subsequent winding, liquid injection, and formation and capacity testing to complete the cell fabrication.

[0111] Cell testing: The first-efficiency capacity of the cells fabricated in the above embodiments and comparative examples is statistically analyzed, and the cycle performance is tested to observe the cycle capacity retention rate and thickness expansion.

[0112] First-efficiency capacity test method: Discharge capacity / (formation charge capacity + charge capacity) = cell first-efficiency.

[0113] Cyclic performance test method: Before testing, test the cell thickness, and then test at 25℃. Charge the cell to the upper voltage limit with a 1C current and constant current and constant voltage, and cut off the current at 0.05C. Then discharge the cell to the lower voltage limit with a 0.5C constant current. Record the discharge capacity. Repeat the charge and discharge steps, and test the cell thickness every 100 cycles with a full charge.

[0114] Cycle capacity retention rate calculation method: Capacity retention rate in week n = Discharge capacity in week n / Initial discharge capacity in week one.

[0115] Thickness expansion rate calculation method: Thickness expansion rate in week n = cell thickness in week n / initial cell thickness - 1.

[0116] Test Results

[0117] First-efficiency capacity data collection:

[0118] Example Capacity (mAh) Initial efficiency Example 1 4282 88.2% Example 2 4378 90.2% Example 3 4540 88.7% Example 4 4735 87.0% Example 5 4952 84.3% Example 6 4980 80.3% Comparative Example 1 4271 87.8% Comparative Example 2 4368 90.0% Comparative Example 3 4524 88.4% Comparative Example 4 4736 87.0% Comparative Example 5 4978 84.7% Comparative Example 6 5042 81.3%

[0119] Loop result:

[0120]

[0121]

[0122] Through the examples and comparative examples, it can be found that in the low-silicon scheme, the capacity and first-efficiency performance are not significantly affected. As the proportion of silicon anode increases, the corresponding positive electrode surface density on one side of the silicon anode also gradually increases, resulting in increased polarization and thus reducing the capacity and first-efficiency performance. Specifically, the improvement of cycling expansion in each example does not significantly worsen the capacity retention rate and first-efficiency performance, while many methods to improve cycling expansion will have a certain impact on the capacity retention rate and first-efficiency performance.

[0123] Cyclic expansion is also affected by the silicon anode content. In the examples and comparative examples with lower silicon content, the expansion is lower and there is a certain expansion improvement effect. As the silicon content increases, the difference is more obvious in the examples with higher silicon content.

[0124] Therefore, by comparing the capacity retention data of the embodiments and comparative examples, it can be found that the embodiments can not only reduce the thickness expansion rate of the battery cell, but also slightly improve the capacity retention rate of the battery cell, because each active material can be matched with its most suitable formula, thereby improving capacity performance. Thickness expansion can be optimized and reduced through the solution of this embodiment.

[0125] It should be understood that the above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit them. Those skilled in the art can modify the technical solutions described in the above embodiments, or make equivalent substitutions for some of the technical features; and all such modifications and substitutions should fall within the protection scope of the appended claims of the present invention.

Claims

1. A negative electrode sheet, characterized in that, It includes a current collector, a silicon anode layer, and a graphite anode layer; the silicon anode layer is laid on one side of the current collector, and the graphite anode layer is laid on the other side of the current collector; the graphite anode layer is formed by roll forming, while the silicon anode layer is not formed by roll forming; the mass ratio of active materials in the silicon anode layer and the graphite anode layer is 5:95 to 50:

50.

2. The negative electrode sheet according to claim 1, characterized in that, The silicon anode layer comprises, by weight percentage, 90%-95% silicon anode, 0%-1% conductive agent, 0%-2% CMC, and 4%-8% binder.

3. The negative electrode sheet according to claim 2, characterized in that, The graphite anode layer comprises, by weight percentage, 95%-98% graphite, 0%-1% conductive agent, 0.5%-2% CMC, and 0.5%-2.5% binder.

4. The negative electrode sheet according to any one of claims 1 to 3, characterized in that, The mass ratio of the active material in the silicon anode layer to that in the graphite anode layer is 5:95 to 30:

70.

5. The negative electrode sheet according to any one of claims 1 to 3, characterized in that, The areal density of the silicon anode layer is 10-40 g / m³. 2 The areal density of the graphite anode layer is 50-200 g / m³. 2 .

6. The negative electrode sheet according to claim 5, characterized in that, The areal density of the graphite anode layer is 126 g / m³. 2 The areal density of the silicon anode layer is 19.2 g / m². 2 .

7. A method for preparing a negative electrode sheet, characterized in that, Including the following steps: Preparation of silicon anode slurry; Preparation of graphite anode slurry; The graphite negative electrode slurry is coated onto one side of the current collector and rolled to obtain a graphite negative electrode layer. The silicon anode slurry is coated onto the other side of the current collector without rolling to obtain a silicon anode layer. The graphite anode layer and the silicon anode layer are dried, and then slit and tab welded to obtain the anode sheet; The mass ratio of the active materials in the silicon anode layer to the graphite anode layer is 5:95 to 50:

50.

8. The preparation method according to claim 7, characterized in that, The silicon anode layer comprises 90%-95% silicon anode, 0%-1% conductive agent, 0%-2% CMC, and 4%-8% binder; the graphite anode layer comprises 95%-98% graphite, 0%-1% conductive agent, 0.5%-2% CMC, and 0.5%-2.5% binder.

9. The preparation method according to claim 7, characterized in that, The areal density of the silicon anode layer is 10-40 g / m³. 2 The areal density of the graphite anode layer is 50-200 g / m³. 2 .

10. A battery cell, characterized in that, It includes the negative electrode, positive electrode, and separator as described in claim 1.

Citation Information

Patent Citations

  • Lithium ion battery negative plate, preparation method and lithium ion battery thereof

    CN115799446A

  • Electrode assembly and secondary battery

    CN115810806A